CUSTOMER RESPONSE INDEX (CRI) TOWARDS “AGAK LAEN” THE MOVIE ADS - Sari, Evi Thelia (UNIVERSITAS INDRAPRASTA PGRI, 2025)
This research aims to describe the Customer Response Index (CRI) towards ‘Agak Laen’ the movie advertisement through its first-seen ad content through the media accessed by audience targets. The topic has novelty in the usage of CRI of movie ads effectiveness and the urgency is to enrich the literature in CRI and movie marketing. Using 232 respondents by purposive sampling, this descriptive quantitative research shows that effectiveness of ‘Agak Laen’ the movie varies regarding the platforms or medias used to advertise. The measurement of ad effectiveness is based on audience targets’ awareness, comprehend, interest, intention and action. The result shows that ‘Agak Laen’ the movie ad through X (Twitter) has the highest level of effectiveness measured by CRI meanwhile Instagram, YouTube, in Cinema, and Netflix are categorized as medium level and the lowest one is ad in TikTok. Although this research is not focusing in factors influencing the effectiveness through platforms, but based on references used the general reasons are about the content and context of the ad and relevancies to platform and its audience characteristics. The factors may be the studied in the further research with more platforms detected used to advertise the movies.